Approaches to the development of durum wheat cultivars (Triticum durum Desf.) with wide variability of the growing season - P. N. Malchikov; M. G. Myasnikova (Вавиловский журнал генетики и селекции)
Differentiation in the duration of growing period is an inherent and, in many respects, decisive factor of task-oriented formation of the cultivar pool in the region. The cause is that one cannot develop a universal cultivar that would be equally effective in utilization of environmental resources and equally responsive to precipitation at different stages of plant growth, to temperature backgrounds, and to the hot wind pattern. That is why the aim of the research is to find ways to extend the range of parameters of the durum wheat growth season in the Middle Volga region. Experiment were conducted to study effects of Vrn genes (1, 2) on the structure and duration of the growth season. Chief parameters of integral production processes were determined with regard to earliness of ripening. The formation of yield components and parameters of the growth season were tested in the Harman’s system of principal components in the context of cultivar adaptivity. The experiments showed that(1) The diversity of durum wheat in the earliness of ripening in the Middle Volga region was determined by pre- dominance of genetic systems other than the system of Vrn genes. (2) Mid-ripening and mid-late genotypes had higher productivity potentials compared to early- ripening ones. In the climatic conditions of the Middle Volga region, it was due to the production of a large foliage surface and photosynthetic potential.(3) The duration of the emergence–heading time span was greatly influenced by the cultivar–air temperature interaction. Opposite responses were recorded in varieties of different ecological and geographic origins, and this should be taken into account in breeding programs. (4) The strongest correlation of yield components and duration of the growth season was observed in groups of non-adapted genotypes. (5) The variation limits of the durum wheat growth season in the Middle Volga region can be extended mainly owing to late-ripening components of cultivar pools.